Terms of trade and Italian economic growth: accounting for miracles - GRILLI, E.; KREGEL, J.A.; SAVONA, P. (PSL Quarterly Review, 2013)
The work argues that post-war political and economic conditions led to the rejection of the pre-war policy of autarchy in favour of an open economy. This decision had implications not only for external trade and payments, but more importantly for the very structure of the Italian industrial sector. The authors show how the performance of this emerging industrial structure was conditioned by the performance of the prices of imported raw material, and subsequently semi-manufactured industrial inputs and the prices at which the final products could be sold in export markets. This so-called industrial terms of trade is combined with the previously existing explanations of post-war growth period that does not have to rely on “miracles” as explanation. JEL: F10, N34, O14